A new Amorphophallus species (Araceae) from Vietnam - Gong, Xun; Li, Heng (Bangladesh Journal of Plant Taxonomy, 2012)
No Abstract DOI: http://dx.doi.org/10.3329/bjpt.v19i2.13136 Bangladesh J. Plant Taxon. 19(2): 201-203, 2012 (December)